Social determinants of alcohol and tobacco use among Hispanic adolescents: a scoping review - Silmi, Kazi Priyanka; Castillo, Victoria; Segura, Nallely; Cervantes, Nayeli Carrillo; Perez, Yailene; Valenzuela, Aubrey; Pugh, Erika A.; Unger, Jennifer B.; Gonzalez, Marybel R. (Frontiers in Psychiatry, 2025)
BackgroundAlcohol and tobacco use (ATU) have been persistent public health concerns among youth in the United States (U.S.), including Hispanic youth who represent 25% of all American youth. While the psychosocial factors associated with ATU among Hispanic adolescents have been investigated for decades, the social environments for youth have undergone considerable change over time. The aim of this scoping review was to examine how social determinants of health (SDOH) influence ATU among Hispanic adolescents and to assess the extent to which mental health variables are integrated into these studies.MethodsWe conducted a systematic, reproducible search on PubMed, PsycInfo, and Scopus for empirical research articles published that examined the SDOH of ATU among Hispanic/Latino/a/x adolescents in the U.S. We retrieved and screened 1467 titles and abstracts that yielded 241 articles for full review, of which 63 articles met final criteria for inclusion in the final synthesis. We categorized the SDOH by domains of behavioral, physical/built environment, socio-cultural, health care, and by levels for individual, interpersonal, school, community, and societal factors.ResultsMost studies focused on socio-cultural domains within individual and interpersonal levels. Less studies examined societal and healthcare domains. Along with the influence of individual and interpersonal determinants (e.g., generational status, Hispanic values, acculturation stress, family and peers), community level factors (e.g., neighborhood level factors such as neighborhood exposure to ATU and neighborhood ethnic concentration) emerged as key structural predictors of ATU. Ethnic discrimination was also identified as a societal level predictor that influenced ATU, with potential association of mental health as mediators, moderators, or co-occurring outcomes. About one-third of the studies investigated the influence of SDOH on ATU along with mental health related variables like depression, anxiety, and stress.ConclusionSDOH at the societal level and in the health care domain were identified as understudied among Hispanic adolescents. Future research is needed on these broader societal and structural determinants, including access to healthcare services and the integration of substance use prevention within these services, to intervene early in adolescence and reduce ATU related health consequences among Hispanic adults in the U.S.